Potential‐Induced Fine‐Tuning of the Enantioaffinity of Chiral Metal Phases. Issue 11 (18th January 2019) - Assavapanumat, Sunpet; Yutthalekha, Thittaya; Garrigue, Patrick; Goudeau, Bertrand; Lapeyre, Véronique; Perro, Adeline; Sojic, Neso; Wattanakit, Chularat; Kuhn, Alexander
Abstract: Concepts leading to single enantiomers of chiral molecules are of crucial importance for many applications, including pharmacology and biotechnology. Recently, mesoporous metal phases encoded with chiral information have been developed. Fine‐tuning of the enantioaffinity of such structures by imposing an electric potential is proposed, which can influence the electrostatic interactions between the chiral metal and the target enantiomer. This allows the binding affinity between the chiral metal and the target enantiomer to be increased, and thus, the discrimination between two enantiomers to be improved. The concept is illustrated by generating chiral encoded metals in a microfluidic channel by reduction of a platinum salt in the presence of a liquid crystal and l ‐tryptophan as a chiral model template. After removal of the template molecules, the modified microchannel retains a pronounced chiral character. The chiral recognition efficiency of the microchannel can be fine‐tuned by applying a suitable potential to the metal phase. This enables the separation of both components of a racemate flowing through the channel. The approach constitutes a promising and complementary strategy in the frame of chiral discrimination technologies. Abstract : In for a shock : The electric potential of a mesoporous chiral platinum phase can be tuned to allow quantitative separation of the enantiomers in a tryptophan racemate. An applied potential influences the electrostatic interactions, and thereby the enantioaffinity, between the chiral metal and the target enantiomer.